Impact of the ditch check dam system over the vegetation coverage of grasslands in the Mixteca region, State of Oaxaca. - Reyes Carrillo, Alejandra; Martínez Menez, Mario Roberto; Rubio Granados, Erasmo; García Moya, Edmundo; Exebio García, Adolfo A. (REVISTA TERRA LATINOAMERICANA, 2019)
In Mexico, the foraging-stock load in pastures is not regulated according to stocking rates, which are estimated in terms of coverage and productivity; this situation has led to the degradation of the vegetation coverage, the reduction of infiltration and water storage capacity in the soil, and the increase of surface runoffs and erosion, which affect the pasture productivity and biomass production, and promote the proliferation of plants with lower palatability and protein quality. Actions to endorse the conservation of soil and water have been implemented in order to mitigate grassland degradation. In this research, the impact of the ditch check dam (DCD) system over the vegetation coverage was evaluated in grasslands of the watershed from rancho Dolores, in the Mixteca region of the State of Oaxaca. Changes in the vegetation coverage were estimated according to percentages of green, dry and total coverage, biomass production, vegetation indexes, and floristic composition in three polygons with DCD at five sampling sites (among-ditch, starting point, ditch, check dam, and foot) and in three polygons without DCD at three sampling sites (upper, central and lower portions). Biomass production in the check dam and ditch was 2.38 Mg ha-1 and 2.29 Mg ha-1 respectively, with significant differences among the following sites: among-ditch, starting point, and foot; the percentages of vegetation coverage, IVPN, NDVI and SAVI did not show significant differences. The control presented significant differences in biomass production and coverage percentage; however, the vegetation indexes did not vary. In areas with DCD, the dominant species was Melinis repens with low forage potential; in control areas, the dominant species was Bouteloua griff ithsii, with regular forage potential. The Multiple Response Permutation Procedure indicated significant differences in the floristic composition among sites with DCD and the control.